Incentivo à Redação Matemática na Educação Básica: O que pensam professores e licenciandos - Bernardo, Raylson José Deodato (2022)
This work addresses the use of mathematical writing as a methodological tool in the classroom by teachers from the city of Aroeiras-PB and how the Licentiate students in Mathematics from the same city are being prepared to work with the writing mathematics in their respective training courses. Our research was qualitative and was carried out through two questionnaires, each one aimed at one of the audiences that were being interviewed. The questions addressed topics related to writing mathematics, their involvement with the Portuguese language and the way in which teachers present a mathematical result to their students. From the questionnaires sent, we obtained responses that indicate a tendency to use mathematical writing as a pedagogical tool, however, due to several factors, some teachers avoid use it. Future teachers, however, indicate that they are not receiving the training expected to be able to use mathematical writing in their range of methodologies. In addition, we investigated how the authors approached the subject through a bibliographic review of the subject.